Modelling of Bonded Post-Tensioned Concrete Cantilever Beams under Flexural Loading - Abbas Mohammed; Khattab Saleem Abdul-Razzaq; Nildem Tayşi; Awat FAQE (Civil Engineering Journal, 2017)
Prestressing is widely used technic all over the world for constructions of buildings, bridges, towers, offshore structures etc. due to its efficiency and economy for achieving requirements of long span with small depth. It is used for flexural strengthening of reinforced concrete structures for improving cracking loads and decreasing deflections due to service loads. There are two methods for prestressing (pre-tensioning and post-tensioning). In this paper, a three-dimensional nonlinear Finite Element (FE) method is used to determine the behaviour of Post-Tensioned (PT) concrete cantilever beams with different tendon profiles. Numerical analyses ANSYS package program is used for analysis of beams. The results from FE analysis is verified by experimental reference test result and good agreement is achieved. This paper is focused on the effect of different tendon profiles on the flexural behaviour of Bonded Post Tensioned (BPT) reinforced concrete cantilever beams. Six models with different tendon profiles are investigated. These models are without tendons, two tendons at the bottom, middle, top, parabolic tendons with one draped point and two draped points. Failure loads, deflections, and load versus deflection relationships for all models are examined and it is seen that the beam with one draped tendon profile shows a highest performance.